Stasiun Kereta Api Tempo Dulu: Perkembangan Stasiun Cimahi Masa Kolonial Belanda 1884-1942 - Dellia Gustiani; Ading Kusdiana; Agung Purnama (Priangan: Journal of Islamic Sundanese Culture, 2025)
The purpose of this article is to conduct research related to the development of Cimahi station during the Nederlandcolonial period in the NederlandIndies. At that time, train transportation itself was one of the main transportations that was widely used for various forms of activities. The method used in this study is the historical research method which has four stages, namely heuristics, source criticism, interpretation and historiography. At the beginning of its development, Cimahi itself was planned to be an area with a train stop as a means of transportation, but over time the Nederland Colonial needed a larger means of transportation, therefore the Cimahi stop experienced an upgrade to a third-class station. After this upgrade, in addition to being a means of passenger transportation, Cimahi station was used as a supporting facility for the Military Garrison and the delivery of garden produce.